Research on the Improvement of New Quality Productivity and Governance Capability - Wang, Xujian; She, Hongyan (Journal of Global Economy, Business and Finance, 2024)
Developing new quality productivity is the internal requirement and important focus of promoting high-quality economic development, and is of great significance for accelerating the realization of Chinese path to modernization. New productive forces are also an effective way to enhance China's grassroots governance capacity and promote the modernization of the national governance system and governance capacity. This article analyzes the connotation and characteristics of new productive forces, and the value and significance of empowering grassroots governance with new productive forces. Analysis shows that in the process of empowerment, there are practical challenges such as low levels of digitalization and intelligence in grassroots governance systems, differences in basic conditions for urban-rural development, weak links in grassroots cultural construction, and urgent need to strengthen grassroots ecological governance capabilities. Therefore, in the process of comprehensively promoting the modernization of grassroots governance, it is necessary to rely on new quality productivity as an empowering element, accelerate the formation of an efficient and transparent governance structure, promote industrial upgrading and resource optimization, enhance digital literacy and cultural life, achieve intelligent monitoring and green development, improve the construction of grassroots governance infrastructure, enhance high-level governance capabilities, and achieve modernization of grassroots governance.